Exploring the Role of Physical Education in Supporting the Motor Development of Primary School Pupils - Nabila, Putri (Jurnal Pendidikan, Kesehatan dan Olahraga, 2024)
The purpose of this study is to evaluate the importance of Physical Education, Sports, and Health in promoting the movement development of elementary school students. A significant concern is the insufficient awareness and understanding among parents regarding the significance of physical education in the growth and development of their children, despite the crucial role parents play in supporting their children's growth and development through home-based training. Moreover, it is worth noting that the lack of participation of educational institutions in promoting children's motor skills is a matter of concern. Hence, it is imperative that parents, educational institutions, and the local community work together to increase awareness and support for physical education in children. This study utilizes a qualitative descriptive methodology to offer comprehensive explanations of both general and specific aspects, as well as scientific methods. Secondary data is employed, sourced from relevant books and journals related to the research topic, as this constitutes a literature review. The role of physical education (PE) is considered strategic as it aims to enhance students' movement experience and development by aligning physical activities with specific goals. By prioritising various types of physical activities and encouraging students to participate, these options aim to educate students on the importance of being active and competitive in achieving academic goals. These activities can help students consistently and effectively improve their basic movement skills. Physical education, sports, and health are considered essential for improving students' movement and social skills. Physical education, sport, and health education aim to contribute to the development of healthy, strong, skilled, hard-working, and adaptable Indonesians.   Physical education, sport, and health education aim to contribute to the development of healthy, strong, skilled, hard-working, and adaptable Indonesians. It is important for teachers to fully utilize the potential of these subjects to encourage the growth and development of their students